2015
DOI: 10.1530/rep-14-0424
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of nephrin in human placental trophoblast syncytialization

Abstract: The placenta has numerous functions, such as transporting oxygen and nutrients and building the immune tolerance of the fetus. Cell fusion is an essential process for placental development and maturation. In human placental development, mononucleated cytotrophoblast (CTB) cells can fuse to form a multinucleated syncytiotrophoblast (STB), which is the outermost layer of the placenta. Nephrin is a transmembrane protein that belongs to the Ig superfamily. Previous studies have shown that nephrin contributes to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…1 A and B) and hCGB (the gene encoding hCGβ) (Fig. 1C), the hallmarks of trophoblast syncytialization (15). STB formation proceeded over time as presented by immunostaining for E-cadherin and DAPI (Fig.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…1 A and B) and hCGB (the gene encoding hCGβ) (Fig. 1C), the hallmarks of trophoblast syncytialization (15). STB formation proceeded over time as presented by immunostaining for E-cadherin and DAPI (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…We reasoned that the trophoblast, especially the STB, could undergo macropinocytosis to keep energy homeostasis and support fast fetal growth in the uterus. First, we performed in vitro trophoblast syncytialization experiments by using two cell models, spontaneously formed STB from PHT cells or forskolin (FSK)-induced cell fusion in the trophoblast cell line BeWo (15). PHT cells, isolated from normal term placenta, fused spontaneously to form STB in 10% FBS-supplemented culture condition, as indicated by a gradually increased expression of Syncytin2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, increased levels of β-hCG and decreased Dysferlin expression observed in PE patients can be attributed to the generation of OS. Further, it is reported that Syncytin-2 is also associated with the immunosuppressive function 52 , a feature crucial for the survival of a semi-allogenic fetus in the maternal endometrial environment and to avoid maternal immune surveillance. Based on the above report, reduced expression of Syncytin2 in ROS-treated trophoblasts and in the placental explants in our study implies that ROS produced in the placental bed could perturb the immune homeostatic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46] Placental Nephrin expression has also been documented in other studies. [47][48][49] The pregnancy phenotype was not caused by an artifact of transgenesis, as none of the many published transgenic mouse lines created using the Nphs1 promoter have reported adverse pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%